The Constitution of Japan and Constitutional Reform. (2nd July 2016) - Inoue, Takeshi
Abstract : Although there have been movements to revise the Constitution of Japan, the original text has remained in effect for 70 years. This article examines the rules of constitutional revision, the basis on which the Constitution was drafted, and the ramifications of an unmodified constitution. Japan's Constitution is compared in terms of length and number of revisions with those of other industrialized countries. The article concludes with recommendations for making Japan's Constitution better able to function in a legal capacity.